ANALISIS EFEKTIVITAS KINERJA KEUANGAN DALAM PENGELOLAAN ANGGARAN PEMERINTAH DAN BELANJA DAERAH PADA KOTA SURABAYA - Aristyanto, Erwan (Jurnal Riset Inossa : Media Hasil Riset Pemerintahan, Ekonomi dan Sumber Daya Alam, 2023)
This study aims to determine the effectiveness of the financial management performance of the Surabaya City Government for the 2015-2019 period. This study uses a quantitative descriptive method using an analysis of the effectiveness of regional financial performance, analysis of regional financial independence and analysis of compatibility (operational expenditure and capital expenditure). Using secondary data, the data processed is the Summary of Regional Revenue and Expenditure Budgets for the 2015-2019 Fiscal Year. The Regional Financial Independence of the Surabaya City Government has reached a very good level, which shows a pattern of delegative relations, which means that the intervention of the Central Government is no longer there because the regions are completely independent in implementing regional autonomy. The level of effectiveness of the Surabaya city government's financial management is fairly effective because from 2015 -2019 the effectiveness of the Surabaya city government's financial performance has always reached the target which is effective. However, the compatibility of the Surabaya government's financial performance has not been balanced. According to the description and calculations above, most of the funds owned by the Surabaya City Government are still prioritized for operational expenditure needs so that the capital expenditure ratio is relatively small.